Islamic Republic of Mauritania : Three-Year Arrangement under the Extended Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Islamic Republic of Mauritania. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses Mauritania's Request for a Three-Year Arrangement Under the Extended Credit Facility (ECF). The economic outlook is positive, but debt remains a concern. Near-term prospects are promising-supported by some improvement in the terms of trade, foreign direct investment in the extractive sector, planned structural reforms, and growth-enhancing public investment. Risks are balanced: on the upside, possible development of a recently discovered off-shore gas field could be a game-changer starting in 2021. On the downside, the economy remains highly vulnerable to lower metals prices, weather-related events, and regional security developments. The IMF staff supports the authorities' request for the ECF arrangement.